PERAN PENDIDIKAN TAUHID DALAM MENINGKATKAN KARAKTER AKHLAKUL KARIMAH DI TK IT AL-GHANIY - Rio Sales, Muhammad; sujarwo, Agus; An An Andari; Setyaningsih, Rina (UNISAN JURNAL, 2024)
negative for the development of early childhood spiritual character. Therefore, an educational concept is needed that can fortify children from these threats. One concept that can be applied is tawhid-based education, this education is based on Islamic religious teachings that unite God. The purpose of this study is to describe the Role of Tawhid Education in improving the Character of Akhlakul Karimah in Al-Ghaniy IT Kindergarten. This research is a case study research that uses a descriptive qualitative method approach with the intention to describe the application of the concept of tawhid-based education and its implications in the formation of children’s spiritual character in depth and detail. The source of the research data was obtained using the purpose sampling technique. The research subjects consisted of kindergarten principals, employees, teachers and children aged 4-5 years in the Al-Ghaniy IT Kindergarten group of 15. From the results of the study, it can be seen that the application of tawhid-based education has proven to play an important role in the formation of early childhood spiritual character through exemplary education, concept cultivation and integrative learning carried out at Al-Ghaniy IT Kindergarten. The key to building children’s spiritual character through the application of this tawhid-based educational curriculum is reading (ber-Iqra’) as stated in QS. al Alaq:1 which is the central value of tawhid which is actualized through the process of Qur’an. There are 3 elements in Iqra’, namely the senses, reason and heart. Thus, these three elements will lead to al Haq (absolute truth). The formation of a child’s spiritual character requires three elements in the Iqra, because the senses, mind and heart can control the behavior of human actions.